2018
DOI: 10.3310/hta22330
|View full text |Cite
|
Sign up to set email alerts
|

Early, specialist vocational rehabilitation to facilitate return to work after traumatic brain injury: the FRESH feasibility RCT

Abstract: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 22, No. 33. See the NIHR Journals Library website for further project information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 109 publications
1
79
0
Order By: Relevance
“…Longitudinal studies which evaluate the co-occurrence and association of post-ICU impairments, predictors or return to work and their effects are needed. Also needed are trials of interventions to facilitate return to work, for example, specialist-led vocational70 or combined cognitive and vocational rehabilitation interventions71 such as those used in survivors of traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies which evaluate the co-occurrence and association of post-ICU impairments, predictors or return to work and their effects are needed. Also needed are trials of interventions to facilitate return to work, for example, specialist-led vocational70 or combined cognitive and vocational rehabilitation interventions71 such as those used in survivors of traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies from Netherlands [36,[47][48][49][50][51][52][53][54][55][56][57] Nine from England [24,[58][59][60][61][62][63][64][65] Six from USA [66][67][68][69][70][71] Five from Scotland [38,39,[72][73][74] Three from Australia [75][76][77] Three from Canada [78][79][80] Two from Germany [81,82] One from Norway [83] One international [16] One UK study [35] More than 4000 patients with a range of LTNCs were in receipt of interventions: stroke featured in 22 studies, dementia in seven, Parkinson's disease in four, multiple sclerosis and mixed LTNCs in three, Huntingdon's disease in two, motor neurone disease and spinal cord injury in a single study each. The complex interventions delivered were:…”
Section: Resultsmentioning
confidence: 99%
“…Exercise-based interventions in twelve [16,50,51,58,67,68,70,71,73,[76][77][78] Home-based rehabilitation in eight studies [35,36,49,52,53,56,60,82] Psychosocial and educational interventions in seven [48,54,57,64,74,75,83] Communication in three [62,72,79] Continence rehabilitation in three [38,61,65] Motor imagery interventions in two [47,59] Constraint-induced movement therapy in two [63,81] Vocational rehabilitation [24], music therapy [55], oral care [84], memory aids [66], bathing [69], selfmanagement [80] in a single study each More than 400 healthcare professionals delivered the interventions and included, in order of prevalence: occupational therapists, physiotherapists, speech and language therapists, psychologists, music therapists, recreational therapists, nurses, physicians, rehabilitation assistants and social workers. Not all studies reported how many professionals, or which profession was involved.…”
Section: Resultsmentioning
confidence: 99%
“…However, respondents were mostly high functioning and more likely to be in work, therefore there is a possible response bias. Three similar studies recorded higher response in usual care participants who have returned to work and conversely poor response from usual care participants who did not return to work (Grant, 2016;Phillips, 2013;Radford et al, 2018). Ways of encouraging participants who do not receive intervention and do not return to work need to be found.…”
Section: Feasibilitymentioning
confidence: 94%